Proposing biologically-based nutrient thresholds for Greek Lakes (2023)
Kemitzoglou D., E. Karadimou, S. Katsavouni, V. Navrozidou, I. Nikolopoulou, M. Seferlis, I. Zerva, and V. Tsiaoussi. 2023. Proposing biologically-based nutrient thresholds for Greek Lakes. Poster presentation in the Symposium for European Freshwater Sciences (SEFS 13), Newcastle University, England, 18 -23 June 2023.